Virtual Reconstruction Of The Architectural Decoration Of Some Churches In Abkhazia (10th to 11th Centuries): Church Of The Assumption In The Village Of Dranda - Endoltseva, Ekaterina; Bystritsky, Nikolai; Dryga, Daniil; Kazennova, Lyubov; Karnaushenko, Alexander
The article discusses the results of a project for the virtual reconstruction of the architectural decoration and small forms of the church in Dranda, Republic of Abkhazia. The available fragments are currently preserved in three locations: the narthex of this church, the Abkhaz State Museum in Sukhumi, and the Ecclesiastical Archaeological Museum of the Holy Metropolis of Abkhazia. In addition, there are published phototypes of two slabs–now lost– with complex multi-figure compositions from the same church. The study and digitization of the existing fragments have brought forward a hypothesis about the original appearance of the altar barrier and the decoration of the western facade of the church in Dranda. The slab which may have adorned the western facade apparently reproduces a fragment of an abbreviated scene of the Last Judgment (Christ on the throne and four angels). Thanks to the stylistic and iconographic analogies, this scene is inscribed in the artistic context of the Christian art of the 10th to 11th centuries.
Keywords: Արվեստագիտական հետազոտություններ